Employing Technological Pedagogical Content Knowledge (TPACK) Skill Among Teachers in Preparing Online School Assessment for Home-Based Learning - Sahrir, Muhammad Sabri Bin; Zaini, Abdul Razif; Hassan, Yaakob; Hamat, Zulkefli; Ismail, Taufik (Ijaz Arabi Journal of Arabic Learning, 2021)
The Technological Pedagogical Content Knowledge (TPACK) framework is crucial for every educators and teachers when dealing with teaching and learning by using technology. There are three essential components of TPACK which have to be fully mastered in order to conduct any teaching and learning session via whatever technological means and platforms, especially in the current situation of COVID-19 pandemic which requires the teacher to adapt with suitable teaching and learning remote strategies including online assessment. This study is conducted to investigate the level of technological pedagogical content knowledge (TPACK) skill among Arabic school teachers in preparing online assessment for remote teaching and learning prior to a training workshop organized by the Malaysian branch of Islamic World Educational, Scientific and Cultural Organization, ICESCO-KUIS and Islamic Education Unit, Ministry of Education, Malaysia. The main author has been conducting the TPACK training module among 56 Arabic school teachers in Johor, Malaysia on 5-6 October, 2020 from selected all districts, while only 40 of them responded to the survey after the workshop via Google Form. Moreover, all participants were responding concurrently to the open-ended survey during the workshop via Mentimeter.com. This research instruments were investigating the teachers’ knowledge about three essential components of TPACK, which include technology, content, and pedagogy as well their suggestions and feedbacks towards employing online assessment and effectiveness of conducted workshop. The findings are expected in contributing towards the understanding of the teacher’s level of knowledge in technology, pedagogy, and content among Arabic school teachers in Malaysia especially for online teaching and assessment. The study may also beneficial to other similar settings where the technology has not been effectively utilized by teachers in schools.